Representasi Krisis Emosional Remaja dalam Musik Video 0x1=Lovesong I Know I Love You Karya Tomorrow X Together Analisis Roland Barthes - Riska Putri Pratami; Ade Budi Santoso (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to reveal the representation of adolescents’ emotional crisis in the music video 0X1=LOVESONG (I Know I Love You) by the South Korean boy group TOMORROW X TOGETHER. Using Roland Barthes’ semiotic approach, the research analyzes the denotative, connotative, and mythical meanings of the visual elements presented in the music video. The main focus is on how emotional crises such as loneliness, instability, alienation, and inner escape are represented through visual symbols such as a dark and messy room, a burning car, and a character standing alone in an open field. The research employed a qualitative descriptive method with a critical paradigm, analyzing eight key scenes in the music video that most strongly depict emotional struggles. The scenes were selected based on their symbolic intensity and relevance to adolescent psychological issues. Data analysis was conducted by interpreting visual signs through Barthes’ concepts of denotation, connotation, and myth. The findings reveal that the music video symbolically narrates the psychological struggles of adolescents who are not only physically isolated but also emotionally detached. The visual symbols construct new meanings that represent the social reality of modern youth, burdened by environmental pressures, societal expectations, and the quest for self-identity. Through the myths it creates, the music video functions not only as a medium of entertainment but also as a reflection and critique of adolescents’ psychological vulnerability. Thus, this study contributes to the understanding of emotional representation in popular media, particularly in audio-visual forms such as music videos, while enriching perspectives on how media constructs the narrative of adolescent emotional crises.